Catalysts for Direct Seawater Electrolysis: Current Status and Future Prospectives - Alei Kasani; Radenka Maric; Leonard Bonville; Stoyan Bliznakov (ChemElectroChem, 2024)
Abstract Global freshwater shortage is forcing researchers to focus on seawater electrolysis for large‐scale green hydrogen production. Seawater purification by reverse osmosis (RO) for use in conventional water electrolyzers (WEs) is another approach, however, that requires large capital investments. Alternatively, seawater can be used directly in a novel type of anion exchange membrane WE (AEMWE) which is currently under development. The AEMWEs have the advantage of using non‐precious catalysts and are less sensitive to the presence of impurities. Success in this early‐stage technology relies on the development of efficient and durable electrocatalysts. This paper provides a comprehensive review of the status and future trends for developing catalysts operating directly with seawater. Catalysts are ranked based on their activity and durability at high current densities of 500 mAcm−2 and 1000 mAcm−2. Notable anode catalysts, S−NiFe2O4, and NiFe LDH, exhibit reduced OER overpotentials of 287 mV and 296 mV at 1000 mAcm−2. Top‐performing cathode HER catalysts include HW−NiMoN‐2 h (132 mV) and Pt−Co−Mo (117 mV) at 1000 mAcm−2. Bifunctional catalysts, such as CoxPv@NC can operate below an overall voltage of 2 V at 1000 mAcm−2. This comparative analysis provides researchers and professionals with critical insights for advancing direct seawater electrolysis.